The Difference between Salivary Viscosity and Salivary Flow Rate on Nicotine Electric Smokers and Non-Smokers - Difaputra, Syavergio Avia; Kusuma, Ira Anggar; Dewi, Dian Puspita; Retnoningrum, Dwi (Universitas Diponegoro, 2025)
Background: Electric cigarette which contained nicotine affected bad impact to oral cavity, since the nicotine contained on e-liquid electric cigarette could reduce function of salivary gland. This condition decreases the salivary flow rate and increase salivary viscosity. could impact to less activity of self-cleansing and antimicrobial of saliva. Objectives: To prove the difference of salivary viscosity and salivary flow rate on nicotine electric smokers and non-smokers. Methods: This research was an analytic descriptive research which exerted cross sectional research design. As many as 60 people were selected to be the research subjects who were then divided into 30 electric smokers and 30 non-smokers. The saliva on each subject was collected in a beaker cup stimulated for 8 minutes, and continued to the viscosity measurement to be valued both visually and subjectively. The data was analyzed through Mann-Whitney test to identify the difference between viscosity and salivary flow rate on nicotine electric smokers and non-smokers. Results: The result of Mann-Whitney test showed a significant difference between salivary flow rate (p<0,05) and salivary viscosity of nicotine electric smokers and non-smokers (p<0,05). Conclusion: This research indicated the difference of viscosity and salivary flow rate between electric smokers and non-smokers. The electric smokers have thicker viscosity and lower flow rate compared to the non-smokers.